Intravenous push administration of anti-seizure medications - Raniah Aljadeed; Raniah Aljadeed; Brian W. Gilbert; Tallib Karaze; Megan A. Rech (Frontiers in Neurology)
Intravenous push (IVP) administration of anti-seizure medications is becoming increasingly popular among emergency departments. IVP administration eliminates the need for compounding and preparation by the pharmacy department, as well as the need to gather infusion materials or set up a patient’s tubing and pump, all of which translate to faster drug administration. This is important given the time-sensitive nature of status epilepticus treatment. This review will discuss several anti-seizure medications, including phenytoin, fosphenytoin, valproic acid, levetiracetam, brivaracetam and lacosamide, for which evidence supports the safe and efficacious use of IV push administration.